2014
DOI: 10.1002/jcc.23694
|View full text |Cite
|
Sign up to set email alerts
|

To be or not to be butterfly: New mechanistic insights in the Aza‐Michael asymmetric addition of lithium (R)‐N‐benzyl‐N‐(α‐methylbenzyl)amide

Abstract: The asymmetric Aza-Michael addition of homochiral lithium benzylamides to α,β-unsaturated esters represents an extended protocol to obtain enantioenriched β-amino esters. An exhaustive mechanistic revision of the originally proposed mechanism is reported, developing a quantum mechanics/molecular mechanics protocol for the asymmetric Aza-Michael reaction of homochiral lithium benzylamides. Explicit and implicit solvent schemes were considered, together with a proper account of long-range dispersion forces, eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Their results suggested that the main potential transition state geometries are two conformers in a "V-stacked" orientation of the lithium amide's phenyl rings. 9…”
mentioning
confidence: 99%
“…Their results suggested that the main potential transition state geometries are two conformers in a "V-stacked" orientation of the lithium amide's phenyl rings. 9…”
mentioning
confidence: 99%